Contrast enhanced pulmonary magnetic resonance angiography for pulmonary embolism: Building a successful program. Issue 3 (March 2016) - Nagle, Scott K.; Schiebler, Mark L.; Repplinger, Michael D.; François, Christopher J.; Vigen, Karl K.; Yarlagadda, Rajkumar; Grist, Thomas M.; Reeder, Scott B.
Highlights: Obtaining consistent high-quality pulmonary embolism MRA studies for Emergency Department patients is feasible. A simple, focused short MRA protocol is essential and is possible using existing commercially available methods. Extending contrast bolus duration to match acquisition length improves image quality. Pulmonary embolism MRA can also show important alternative diagnoses. Artifacts on MRA that differ from those on CTA are described. Strategies for overcoming potential barriers to implementation of a clinical pulmonary embolism MRA program are described. Abstract: The performance of contrast enhanced pulmonary magnetic resonance angiography (MRA) for the diagnosis of pulmonary embolism (PE) is an effective non-ionizing alternative to contrast enhanced computed tomography and nuclear medicine ventilation/perfusion scanning. However, the technical success of these exams is very dependent on careful attention to the details of the MRA acquisition protocol and requires reader familiarity with MRI and its artifacts. Most practicing radiologists are very comfortable with the performance and interpretation of computed tomographic angiography (CTA) performed to detect pulmonary embolism but not all are as comfortable with the use of MRA in this setting. The purpose of this review is to provide the general radiologist with the tools necessary to build a successful pulmonary embolism MRA program. This review will cover in detail image acquisition, image interpretation, and some key elements of outreach that help to frame the role of MRA to consulting clinicians and hospital administrators. It is our aim that this resource will help build successful clinical pulmonary embolism MRA programs that are well received by patients and physicians, reduce the burden of medical imaging radiation, and maintain good patient outcomes.